PERSEPSI MAHASISWA TERHADAP APLIKASI “KORE WA NANI” SEBAGAI MEDIA PEMBELAJARAN MEMBACA KANJI II - Ahmad Kurniawan; Frida Philiyanti; Yuniarsih (Universitas Negeri Jakarta, 2026)
Learning kanji in Japanese is often a major challenge for learners, primarily due to visual complexity, the large number of characters, and differences in reading methods (onyomi and kunyomi). The advent of smartphone applications has revolutionized language learning, offering innovative solutions to address these challenges. The